2017
DOI: 10.3389/fsurg.2017.00062
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Laparoscopic Closure of the Linea Alba with Barbed Sutures Combined with Laparoscopic Mesh Implantation (IPOM Plus Repair) As a New Technique for Treatment of Abdominal Hernias

Abstract: Despite extensive experience and significant reduction of complications in recent years, laparoscopic treatment of complex abdominal hernias is a challenge even for the experienced endoscopic surgeon. Patients with severe incisional hernias or symptomatic rectus diastasis benefit from the closure of the linea alba as a morphological and physiological reconstruction of the abdominal wall followed by mesh implantation. Occasionally, an additional component separation is necessary. In open surgery, this is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The defect was then closed by a running suture in a caudal to cranial direction, with tissue bites and inter-suture spacing of 1 cm each. The suture intervals were comparable to those described in previous reports (2,4,12). As the BS was 45 cm in length, this maneuver was facilitated by pulling the needle holder out of the trocar at Palmer's point ( Figure 2).…”
Section: Materials and Surgical Techniquesupporting
confidence: 80%
See 2 more Smart Citations
“…The defect was then closed by a running suture in a caudal to cranial direction, with tissue bites and inter-suture spacing of 1 cm each. The suture intervals were comparable to those described in previous reports (2,4,12). As the BS was 45 cm in length, this maneuver was facilitated by pulling the needle holder out of the trocar at Palmer's point ( Figure 2).…”
Section: Materials and Surgical Techniquesupporting
confidence: 80%
“…We limited the maximum diameter of the defect to 6 cm to avoid excessive tension after the fascial closure. In recent studies, intracorporeal defect closure was preferably indicated for defects less than or equal to 10 cm, whereas extracorporeal closure, with relaxing incision or the endoscopic anterior component separation, was performed for larger defects (greater than 10 cm) . Accordingly, we may be able to extend the application of our technique to defects up to 10 cm.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several different placements of trocars are used, most commonly suprapubic and periumbilical (26, 29, 3234) or suprapubic and in both iliac fossae (28, 30, 35, 36). Four studies included patients with ventral hernia, specified as umbilical, epigastric, supraumbilical, or incisional hernia (28, 33, 35, 36). As during open approach, the repair of the rectus fascia can be performed with or without mesh reinforcement.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…In laparoscopic incisional hernia repair, IPOM plus repair involves the performance of IPOM repair after suture the abdominal wall defect. Comparing the two approaches, some investigations have suggested that IPOM plus repair reduces recurrence rate, the risk of seroma, and mesh bulge [ 23 26 ]. We acknowledge that IPOM plus repair may reduce the recurrence rate of umbilical hernia.…”
Section: Discussionmentioning
confidence: 99%